Stem Cell Therapy in Treating Epilepsy - Chang, Bao-Luen; Chang, Kuo-Hsuan (Frontiers in Neuroscience, 2022)
Epilepsy is a common disabling chronic neurological disorder characterized by enduring propensity for generation of seizures which result from abnormal hypersynchronous firing of neurons in the brain. Over 20-30% of epilepsy patients fail to achieve seizure control or soon become resistant to current available therapies. Prolonged seizures or uncontrolled chronic seizures would give rise to neuronal damage or death, astrocyte activation, reactive oxygen species production, and mitochondrial dysfunction. Stem cell therapy is potentially a promising novel therapeutic strategy for epilepsy. The regenerative properties of stem cell-based treatment provide an attractive approach for long term seizure control, particularly in drug-resistant epilepsy. Embryonic stem cells (ESCs), mesenchymal stem cells (MSCs), neural stem cells (NSCs), induced pluripotent stem cells (iPSCs), and adipose-derived regenerative cells (ADRCs) are capable of differentiating into specialized cell types has been applied for epilepsy treatment in preclinical animal research and clinical trials. In this review, we will focus on the advances of stem cell therapy for epilepsies. The goals of stem cell transplantation, its mechanisms underlying graft effects, the types of grafts and their therapeutic effects. The cell and animal models used for investigating stem cell technology in epilepsy treatment are summarized.